2017
DOI: 10.1007/s00438-017-1291-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of transposable elements in the coffee berry borer Hypothenemus hampei (Coleoptera: Curculionidae): description of novel families

Abstract: The coffee berry borer (CBB) Hypothenemus hampei is the most limiting pest of coffee production worldwide. The CBB genome has been recently sequenced; however, information regarding the presence and characteristics of transposable elements (TEs) was not provided. Using systematic searching strategies based on both de novo and homology-based approaches, we present a library of TEs from the draft genome of CBB sequenced by the Colombian Coffee Growers Federation. The library consists of 880 sequences classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 71 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…Hernandez-Hernandez et al . 39 characterized the TEs present in the CBB genome, revealing that 11.51% of the TEs belong to the Tc1/mariner superfamily. Furthermore, the authors confirmed that at least 8.2% of the CBB genome is composed of TEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hernandez-Hernandez et al . 39 characterized the TEs present in the CBB genome, revealing that 11.51% of the TEs belong to the Tc1/mariner superfamily. Furthermore, the authors confirmed that at least 8.2% of the CBB genome is composed of TEs.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed by Hernandez-Hernandez et al . 39 , insect reproductive characteristics may be related to low TE content. Haplodiploidy, in which a chromosome set from males is not transmitted to the next generation, prevents the spread of certain TE genes.…”
Section: Discussionmentioning
confidence: 99%
“…Within the largest insect order, Coleoptera, very little is known regarding TE distribution and evolution. T. castaneum harbors only 6% of TEs (Tribolium Genome Sequencing Consortium et al 2008), Hypothenemus hampei contains 8.2% of TEs (Vega et al 2015; Hernandez-Hernandez et al 2017), while Dichotomius schiffleri harbors 21% (Ic et al 2020). The species closest to S. oryzae , Rhynchophorus ferrugineus, has a TE content of 45% (Hazzouri et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The S. oryzae genome is among the most TE-rich insect genomes to date little is known regarding TE distribution and evolution. T. castaneum harbors only 6% of TEs [53], Hypothenemus hampei contains 8.2% of TEs [6,95], while Dichotomius schiffleri harbors 21% [96]. The species closest to S. oryzae, Rhynchophorus ferrugineus, has a TE content of 45% [8].…”
Section: Odorant Receptorsmentioning
confidence: 99%
“…TE excision can lead to DNA deletions [41], and TE insertion can result in adding DNA through 3 0 and, less frequently, through 5 0 transduction [42,43]. Finally, ectopic recombination between TEs causes [12], >66% [13]) Mus musculus [143], Saccharomyces cerevisiae [144], Arabidopsis thaliana [145], Pyrococcus furiosus [146], Clostridium difficile [147], Danio rerio [133], Kryptolebias marmoratus [148], Bombyx mori [149], Hypothenemus hampei [150], Drosophila melanogaster (11%, [68],~20% [69]), Pseudozyma antarctica, and Laccaria bicolor [151]. Zea mays [152] and Fritillaria imperialis [8].…”
Section: Transposable Elements Are Abundant and Active Genome Denizensmentioning
confidence: 99%